The Removal of Pharmaceuticals and Personal Care Products (PPCPs) as Mixture from Water Stream by Ozonation: The Effect of pH and Retention Time on PPCPs Removal - Hind M. Ewadh (Journal of Global Pharma Technology, 2018)
Pharmaceuticals and personal care products (PPCPs) can be found in waste water and even sometimes in drinking water with increasing in the concentration especially within this last decade due to the high usage of medicines in daily life. Ketoprofen (KET) and Ibuprofen (IBU), as an anti-inflammatory drug, 17α- ethinylestradiol (EE2) as synthetic estrogen and Galaxolide (HHCB) as personal care products are found in many water sources with different concentration and they are unremovable by the conventional wastewater treatment and can be found in tap or drinking water. In this research, ozonation was used as removal technique to remove these PPCPs as a mixture by varying the ozonation contact between 15, 22.5 and 30 min and changing in pH value between 6, 7.5 and 9. After ozonation, the removal was recorded between (75-100%) for the selected PPCPs. During the ozonation pH was monitored decreasing in value and degradation occurred and transformed products were detected by GC/MS. Thus, ozonation can be used to remove the PPCPs from the water stream and the highest removal was conducted at pH= 9.Keywords: Pharmaceuticals and personal care products, Ibuprofen, Ketoprofen, 17α-ethinylestradiol, Galaxolide, Ozonation.